Modified zinc oxide nanofiber as well as preparation method and application thereof
By modifying zinc oxide nanofibers to detect 3 hydroxy-2 butanone gas, the existing Listeria detection methods and equipment are solved, and the rapid and highly sensitive detection of Listeria is achieved, and the ZnO gas is improved. Sensitivity and selectivity of sensors.
Patent Information
- Application Number
- CN202411255729.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-20
AI Technical Summary
The existing Listeria detection methods and equipment are expensive, time-consuming, low sensitivity, and strict experimental conditions, which cannot meet the needs of rapid and sensitive detection of pathogenic bacteria in food.
Modified zinc oxide nanofibers are used to detect 3 hydroxy-2 butanone gas to achieve the detection of Listeria, which improves the sensitivity and selectivity of ZnO gas sensors. The preparation method includes adding poly(N,N-dimethylformamide) to N,N-dimethylformamide. Vinylpyrroleenone and zinc acetate dihydrate were electrospinned, dried and calcined to form In-ZnO nanofibers.
Fast and highly sensitive detection of Listeria is achieved. In-ZnO nanofibers have fast response speed to 3H-2B gases, high sensitivity, high selectivity, response speed up to 1s and sensitivity up to 830, suitable for real-time monitoring of Listeria. Special bacteria.
Smart Images

Figure CN119162705A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microbial monitoring, and specifically relates to a modified zinc oxide nanofiber and a preparation method and application thereof. Background Art
[0002] Food safety problems caused by foodborne pathogens such as Listeria monocytogenes are frequent. Listeria is known as the "refrigerator killer". Compared with other foodborne pathogens, it has a much higher tolerance to low temperatures. Listeria monocytogenes is often detected in refrigerated foods and raw poultry. Infection with Listeria can cause fever, headache and gastrointestinal manifestations such as vomiting, nausea and diarrhea in mild cases, and serious complications may occur in severe cases, including meningoencephalitis, sepsis, endocarditis, etc., with a mortality rate of up to 20%-30%. Rapid and highly sensitive detection of Listeria is the key to timely cutting off the transmission path of Listeria and preventing and treating diseases such as meningitis and endocarditis caused by Listeria.
[0003] Currently, methods for detecting Listeria include nucleic acid detection, real-time PCR, isolation and culture biochemical identification (USDA, FDA, IDF), immunological methods (ELISA, IGLT), mass spectrometry, etc., which are not only time-consuming but also require expensive equipment. The FDA method is to first culture the sample for bacterial enrichment, take a portion of the enrichment solution and incubate it on LPM agar / LPM agar + esculin + Fe 3+The method is to separate and culture the bacteria in culture medium / PALCAM culture medium, or separate and culture the single colony on Oxford agar (OXA) plate with the enriched culture medium, and finally culture the culture medium in tryptic soy agar + 0.6% yeast extract and perform biochemical and serological verification tests on the cultured bacteria. This method is cumbersome to operate, has a large workload, and a long detection cycle (generally 4-7 days). In this cumbersome process, any error in any link may affect the identification results of the bacteria, and the sensitivity is low, and the missed detection and false detection rates are high. In addition, this method has strict requirements on experimental conditions, so it cannot meet the needs of rapid and sensitive detection of pathogenic bacteria in food. Immunocolloidal gold technology (IGLT) is a detection technology developed in the 1970s. This technology uses colloidal gold as a tracer marker for antigen-antibody reaction. Although immunocolloidal gold technology has the advantages of simple operation, low cost, and easy to carry, most immunocolloidal gold technologies use monoclonal antibodies to ensure their specificity, have the disadvantages of low sensitivity, and the detection results are easily affected by the experimental environment. PCR is a molecular biology technique based on nucleic acid molecular hybridization for amplifying specific DNA fragments. It includes ordinary PCR, nested PCR, fluorescent quantitative PCR, multiplex PCR, RT-PCR and immune PCR. The high specificity of PCR reaction is attributed to the high specificity of primers, so for PCR reaction, the design of primers is particularly critical. If the design is unreasonable, false negative and false positive results are prone to occur. In addition, the expensive reagents and the need for pre-enrichment of samples are also disadvantages that cannot be ignored in this detection method.
[0004] Among various gas sensors, metal oxide semiconductors have attracted much attention due to their high response, low cost, environmental protection and portability. ZnO, as a typical n-type metal oxide semiconductor, has attracted much attention due to its excellent electronic properties, flexible preparation and non-toxicity. However, the sensitivity and selectivity of pure ZnO are low. Noble metal modification, heterostructure construction and doping are effective methods to enhance the gas sensing performance of ZnO. Summary of the invention
[0005] In view of the shortcomings of existing Listeria detection methods such as expensive equipment and long time consumption, the present invention provides a modified zinc oxide nanofiber and a preparation method thereof, and utilizes the modified zinc oxide nanofiber to detect 3-hydroxy-2-butanone (3H-2B) gas, thereby realizing a method for detecting Listeria and improving the sensitivity and selectivity of ZnO gas sensors.
[0006] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0007] According to a first aspect of the present invention, there is provided a modified zinc oxide nanofiber obtained by the following preparation method:
[0008] S1. Add polyvinyl pyrrolidone (PVP) to N,N-dimethylformamide (DMF), and then add zinc acetate dihydrate and hydrated indium nitrate after dissolving evenly, and stir at high speed to dissolve evenly.
[0009] S2, electrospinning the precursor solution obtained in S1;
[0010] S3, drying the film obtained in S2;
[0011] S4, calcining the film obtained in S3.
[0012] According to a second aspect of the present invention, there is provided a method for preparing modified zinc oxide nanofibers, comprising:
[0013] S1. Add polyvinyl pyrrolidone (PVP) to N,N-dimethylformamide (DMF), and then add zinc acetate dihydrate and hydrated indium nitrate after dissolving evenly, and stir at high speed to dissolve evenly.
[0014] S2, electrospinning the precursor solution obtained in S1;
[0015] S3, drying the film obtained in S2;
[0016] S4, calcining the film obtained in S3.
[0017] For the above-mentioned modified zinc oxide nanofiber and its preparation method:
[0018] Preferably, in S1, the mass ratio of the N,N-dimethylformamide (DMF) to the polyvinylpyrrolidone (PVP) is (10-11):1.
[0019] Preferably, in S1, the mass ratio of the zinc acetate dihydrate to the polyvinyl pyrrolidone (PVP) is (1-2):1.
[0020] Preferably, in S1, the molar ratio of In in the hydrated indium nitrate to Zn in the zinc acetate dihydrate is ≤7% and is not 0%.
[0021] Preferably, in S2, the feed rate of the electrospinning is 0.1-0.3 ml / h, the voltage is 13-18 kV, the distance from the needle to the collecting drum is 11-15 cm, and the drum speed is 800-1000 rpm.
[0022] Preferably, in S3, the drying process is carried out at a temperature of 60-100°C and for a time of 36-48 hours.
[0023] Preferably, in S4, the calcination process is to increase the temperature to 500-700°C at a heating rate of 1-3°C / min, and keep the temperature for 2-4h, and then naturally cool to room temperature.
[0024] According to a third aspect of the present invention, there is provided an application of the modified zinc oxide nanofibers described above, wherein the modified zinc oxide nanofibers are used to detect 3-hydroxy-2-butanone gas, a biomarker of Listeria.
[0025] The beneficial effects of the present invention are:
[0026] The (0.5%-7%) In-ZnO nanofibers prepared by this method have excellent gas-sensing performance for the biomarker 3H-2B, fast response speed, and high sensitivity. 3H-2B gas is a biomarker of Listeria metabolism. The present invention monitors Listeria by detecting 3H-2B gas through In-ZnO nanofibers, which provides the possibility for real-time monitoring of Listeria and has great application potential. Among them, the diameter of 3% In-ZnO nanofibers is about 35nm. The gas-sensing performance test results show that the material has high selectivity, a response speed of up to 1s, and a sensitivity of up to 830. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The figure is a flow chart of the preparation of the In-doped ZnO nanofiber and the gas sensor thereof of the present invention;
[0028] Figure 2 The response curves of the gas sensors prepared from the samples obtained in Examples 1-6 of the present invention to 100 ppm 3H-2B at different operating temperatures;
[0029] Figure 3 The response curve of the gas sensor prepared from the samples obtained in Examples 1-6 of the present invention to 3H-2B gas of different concentrations at 170°C;
[0030] Figure 4 The continuous dynamic response-recovery curve diagram of the gas sensor prepared from the sample obtained in Example 4 of the present invention to different concentrations of 3H-2B (1-200 ppm) at 170°C;
[0031] Figure 5 The linear fitting relationship between the response of the gas sensor prepared from the sample obtained in Example 4 of the present invention to different concentrations of 3H-2B (1-200 ppm) at 170° C. and the gas concentration;
[0032] Figure 6 The dynamic response-recovery curve of the gas sensor prepared from the sample obtained in Example 4 of the present invention to 100 ppm 3H-2B at 170°C;
[0033] Figure 7 This is a graph showing five sensitivity cycles of the gas sensor prepared from the sample obtained in Example 4 of the present invention to 100 ppm 3H-2B at 170°C;
[0034] Figure 8 This is a graph showing the selectivity test results of the gas sensor prepared from the sample obtained in Example 4 of the present invention for 9 gases at 100 ppm at 170°C;
[0035] Fig. 9 This is a long-term stability test diagram of a gas sensor prepared from a sample obtained in Example 4 of the present invention;
[0036] Fig.10 BET test results of (a) pure ZnO nanofibers and (b) 3% In-ZnO nanofibers;
[0037] Fig.11 Schematic diagram of the gas sensor prepared from the sample obtained in Example 4 of the present invention for detecting 3H-2B;
[0038] Fig.12 This is the bandgap width test diagram of pure ZnO nanofibers and 3% In-ZnO nanofibers. DETAILED DESCRIPTION
[0039] The following is a more detailed description of the specific implementation of the present invention in conjunction with the accompanying drawings and embodiments, so as to better understand the scheme of the present invention and its advantages in various aspects. It should be noted that the specific implementation methods and embodiments described below are only for the purpose of illustration, and are not intended to limit the present invention.
[0040] like Figure 1 As shown, the present invention adds DMF and PVP to a sample bottle, stirs at high speed until PVP is evenly dissolved, then adds zinc acetate dihydrate and a certain molar fraction of hydrated indium nitrate, stirs at high speed again to mix evenly, transfers the solution to a syringe, and fixes it on a peristaltic pump for electrostatic spinning. After electrospinning, remove the sample film and dry it in a blast drying oven. After the dried sample is calcined in a muffle furnace, it is naturally cooled to room temperature. The collected samples are labeled as ZnO, 0.5% In-ZnO, 1% In-ZnO, 3% In-ZnO, 5% In-ZnO, and 7% In-ZnO.
[0041] For some preferred embodiments of the present invention, in S1, the mass ratio of N,N-dimethylformamide (DMF) to polyvinylpyrrolidone (PVP) is (10-11):1.
[0042] For some preferred embodiments of the present invention, in S1, the mass ratio of zinc acetate dihydrate to polyvinyl pyrrolidone (PVP) is (1-2):1.
[0043] For some preferred embodiments of the present invention, in S1, the molar ratio of In in the hydrated indium nitrate to Zn in the zinc acetate dihydrate is ≤7% and is not 0%.
[0044] For some preferred embodiments of the present invention, in S2, the feed rate of electrospinning is 0.1-0.3 ml / h, the voltage is 13-18 kV, the distance from the needle to the collecting drum is 11-15 cm, and the drum speed is 800-1000 rpm.
[0045] For some preferred embodiments of the present invention, in S3, the drying process is carried out at a temperature of 60-100°C and for a time of 36-48 hours.
[0046] For some preferred embodiments of the present invention, in S4, the calcination process is to increase the temperature to 500-700°C at a heating rate of 1-3°C / min, and keep the temperature for 2-4h, and then naturally cool to room temperature.
[0047] Specifically:
[0048] Embodiment 1:
[0049] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.
[0050] Step 2: Add 1 g of zinc acetate dihydrate to the obtained uniform solution, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.
[0051] Step 3: Transfer the obtained solution into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine, set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 13 cm, and the drum speed to 800 rpm.
[0052] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.
[0053] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 1°C / min, heat to 500°C and keep it for 2 hours, then let it cool naturally to room temperature; collect the sample and mark it as ZnO.
[0054] Embodiment 2:
[0055] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.
[0056] Step 2: Add 1 g of zinc acetate dihydrate and hydrated indium nitrate with In (mol) / Zn (mol) = 0.5% to the obtained uniform solution, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.
[0057] Step 3: Transfer the obtained solution into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine, set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 13 cm, and the drum speed to 800 rpm.
[0058] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.
[0059] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 1°C / min, heat to 500°C and keep it for 2 hours, then let it cool naturally to room temperature; collect the sample and mark it as 0.5% In-ZnO.
[0060] Embodiment 3:
[0061] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.
[0062] Step 2: Add 1 g of zinc acetate dihydrate and hydrated indium nitrate with In (mol) / Zn (mol) = 1% to the homogeneous solution obtained above, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.
[0063] Step 3: Transfer the solution obtained in step 2 into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine. Set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 13 cm, and the drum speed to 800 rpm.
[0064] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.
[0065] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 1°C / min, heat to 500°C and keep it for 2 hours, then let it cool naturally to room temperature; collect the sample and mark it as 1% In-ZnO.
[0066] Embodiment 4:
[0067] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.
[0068] Step 2: Add 1 g of zinc acetate dihydrate and hydrated indium nitrate with In (mol) / Zn (mol) = 3% to the homogeneous solution obtained above, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.
[0069] Step 3: Transfer the solution obtained in step 2 into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine. Set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 13 cm, and the drum speed to 800 rpm.
[0070] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.
[0071] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 1°C / min, heat to 500°C and keep it for 3 hours, then let it cool naturally to room temperature; collect the sample and mark it as 3% Co-ZnO.
[0072] Embodiment 5:
[0073] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.
[0074] Step 2: Add 1 g of zinc acetate dihydrate and hydrated indium nitrate with In (mol) / Zn (mol) = 5% to the homogeneous solution obtained above, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.
[0075] Step 3: Transfer the solution obtained in step 2 into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine. Set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 13 cm, and the drum speed to 800 rpm.
[0076] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.
[0077] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 1°C / min, heat to 500°C and keep it for 2 hours, then let it cool naturally to room temperature; collect the sample and mark it as 3% Co-ZnO.
[0078] Embodiment 6:
[0079] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.
[0080] Step 2: Add 1 g of zinc acetate dihydrate and hydrated indium nitrate with In (mol) / Zn (mol) = 7% to the homogeneous solution obtained above, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.
[0081] Step 3: Transfer the solution obtained in step 2 into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine. Set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 13 cm, and the drum speed to 800 rpm.
[0082] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.
[0083] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 1°C / min, heat to 500°C and keep it for 3 hours, then let it cool naturally to room temperature; collect the sample and mark it as 5% Co-ZnO.
[0084] Weigh 10-20 mg of the samples prepared in Examples 1-6 into a mortar, add a small amount of distilled water, and grind them thoroughly into a paste. Then, use a clean fine brush to evenly apply the paste on the ceramic tube of the gas sensor, dry it at 80°C for 5 hours, and then age it on an AS-20 aging device with a current of 80 mA for 48 hours to obtain six gas sensors to be tested.
[0085] Figure 2 The responses of six gas sensors are shown as a function of operating temperature. Figure 2 As shown in the figure, with the increase of working temperature, except for ZnO, the sensitivity of each gas sensor shows a trend of first increasing and then decreasing. The optimal working temperature of the six sensors is 170℃. Under the optimal working temperature conditions, the responses of ZnO, 0.5% In-ZnO, 1% In-ZnO, 3% In-ZnO, 5% In-ZnO, and 7% In-ZnO to 100ppm 3H-2B are 40.586, 335.879, 450, 830, 240, and 560, respectively. Among them, 3% In-ZnO has the highest sensitivity, while ZnO has the lowest response, indicating that In doping significantly improves the sensing performance of pure ZnO.
[0086] Figure 3The responses of six gas sensors to different concentrations of 3H-2B at 170°C are shown. Figure 3 As shown in the figure, the response of each sensor increases linearly with the increase of 3H-2B concentration. In the range of 20-200ppm, 3% In-ZnO has the highest response to 3H-2B, and its response to 100ppm 3H-2B is 20.45 times that of ZnO, indicating that In doping significantly enhances the sensing of ZnO nanofibers. The responses of 3% In-ZnO nanofibers to 1, 2, 5, 10, 20, 50, 100 and 200ppm 3H-2B are 3.067, 4.446, 11.409, 32.823, 137.999, 361.923, 824.28 and 1576.276, respectively.
[0087] Figure 4 The following is a continuous dynamic response-recovery curve of the gas sensor prepared from the sample obtained in Example 4 at 170°C to different concentrations of 3H-2B (1-200 ppm). Figure 4 As shown in the figure, with the increase of 3H-2B concentration, the response of 3% In-ZnO is enhanced, showing excellent cycle stability performance.
[0088] The response of the gas sensor prepared by 3% In-ZnO to different concentrations of 3H-2B was evaluated by linear regression analysis. The linear fitting relationship between the response and the gas concentration is shown in Figure 5 The fitted linear equation is y=8.06192x–21.92516, and the correlation coefficient (R) is 0.99829, indicating that there is a good linear relationship between the sensor's response to different concentrations of 3H-2B and the gas concentration.
[0089] Figure 6 The dynamic response-recovery curve of the gas sensor prepared from the sample obtained in Example 4 of the present invention to 100 ppm 3H-2B at 170°C. Figure 6 As shown in the figure, at 170°C, the response time of 3% In-ZnO nanofibers to 100ppm 3H-2B is 1s. Due to the low operating temperature and strong gas adsorption, the sensor recovery time is long. Thermal pulses are used to assist the device in recovery. The specific operation is to switch the heating current to 150mA first. When the sensor resistance begins to rise, it means that gas desorption begins. At this time, the heating current is switched back to 100mA. The use of thermal pulses greatly shortens the recovery time of the device, which is more conducive to the practical application of Listeria detection.
[0090] At 170°C, 3% In-ZnO was used to perform dynamic response-recovery tests on 100ppm 3H-2B for 5 consecutive times. The test results are shown in Figure 2. Figure 7After 5 cycles, the sensor showed good stability and recovery ability in response to 3H-2B, and the overall response remained basically unchanged. Figure 6 As mentioned above, heat pulses were used throughout the cycle to assist the device in recovery, which further illustrates the excellent stability of the sensor.
[0091] Figure 8 The responses of gas sensors made of ZnO, 0.5% In-ZnO, 1% In-ZnO, 3% In-ZnO, 5% In-ZnO and 7% In-ZnO to 9 target gases at 100ppm at 170°C are shown. It can be seen that ZnO has the highest response to triethylamine, while In-ZnO has the highest response to 100ppm 3H-2B, indicating that In doping improves the selectivity of ZnO to 3H-2B. Among them, the response value of 3% In-ZnO nanofibers to 3H-2B is 830, and the response values to acetone, triethylamine, methanol, ethanol, benzene, n-butanol, isopropanol and toluene are 26.51, 47.33, 11.81, 8.98, 37.44, 54.26, 30.87 and 51.74 respectively.
[0092] In order to test the long-term stability of the sensor, the gas sensor prepared with 3% In-ZnO was tested for its response to 100ppm 3H-2B at 170°C for 15 consecutive days. Fig. 9 As shown, it can be seen that the response of the sensor fluctuates slightly within 15 days, showing excellent long-term stability.
[0093] The specific surface area and pore size distribution of ZnO nanofibers and 3% In-ZnO nanofibers were studied using N2 adsorption-desorption technology. The BET test results are shown in Fig.10 As shown in the test results, the specific surface area of ZnO is 19.157m 2 / g, while the specific surface area of 3% In-ZnO is slightly larger, which is 22.601m 2 / g. This means that in the gas sensing process, 3% In-ZnO can provide more active sites for gas molecules, thereby achieving higher sensitivity. According to the IUPAC standard, the pore type of ZnO and 3% In-ZnO is H3 type, with plate seams, cracks, and wedge-shaped structural characteristics. In addition, the pore volume-pore distribution curve shows that the most probable pore size of 3% In-ZnO is 2.8259nm, which is smaller than 3.4625nm of pure ZnO.
[0094] Fig.11Schematic diagram of the gas sensor prepared from the sample obtained in Example 4 of the present invention for detecting 3H-2B. When the temperature is lower than 150°C, the oxygen adsorbed on the surface of MOS mainly exists in the form of O2-; in the range of 150°C-400°C, the adsorbed oxygen of the sensitive material is mainly O-; when the temperature is higher than 400°C, the adsorbed oxygen is mainly O2-. 3% In-ZnO has the characteristics of n-type MOS and conducts electricity mainly through electrons. Since oxygen has a strong electronegativity in the air, oxygen molecules will be adsorbed on the surface of 3% In-ZnO and react with electrons in its conduction band to form oxygen ions. As shown in the figure, at 170°C, the oxygen adsorbed on the surface of 3% In-ZnO is mainly O-, resulting in the formation of an electron depletion layer (EDL) on the surface of 3% In-ZnO, which increases its resistance and grain boundary barrier. When the sensor detects 3H-2B, the adsorbed oxygen ions react with the 3H-2B molecules, releasing electrons back into the material, reducing the EDL width and grain boundary barrier, while reducing the resistance.
[0095] Fig.12 The figure shows the bandgap width test of pure ZnO nanofibers and 3% In-ZnO nanofibers. The UV-Vis test results show that the bandgap width of 3% In-ZnO is 3.12eV, while the bandgap width of pure ZnO nanofibers is 3.22eV, which means that under the same temperature conditions, 3% In-ZnO nanofibers will be able to excite more carriers and exchange electrons with more oxygen, thereby effectively enhancing the gas sensing performance.
[0096] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the invention and the claims, all of which fall within the scope of protection of the present invention.
Claims
1. A method for preparing modified zinc oxide nanofibers, characterized in that: include: S1. Add polyvinyl pyrrolidone (PVP) to N,N-dimethylformamide (DMF), and then add zinc acetate dihydrate and hydrated indium nitrate after dissolving evenly, and stir at high speed to dissolve evenly. S2, electrospinning the precursor solution obtained in S1; S3, drying the film obtained in S2; S4, calcining the film obtained in S3.
2. The method for preparing modified zinc oxide nanofibers according to claim 1, characterized in that: In S1, the mass ratio of the N,N-dimethylformamide (DMF) to the polyvinylpyrrolidone (PVP) is (10-11):
1.
3. The method for preparing modified zinc oxide nanofiber according to claim 1, characterized in that: In S1, the mass ratio of the zinc acetate dihydrate to the polyvinyl pyrrolidone (PVP) is (1-2):
1.
4. The method for preparing modified zinc oxide nanofibers according to claim 1, characterized in that: In S1, the molar ratio of In in the hydrated indium nitrate to Zn in the zinc acetate dihydrate is ≤7% and is not 0%.
5. The method for preparing modified zinc oxide nanofiber according to claim 1, characterized in that: In S2, the feed rate of the electrospinning is 0.1-0.3 ml / h, the voltage is 13-18 kV, the distance from the needle to the collecting drum is 11-15 cm, and the drum speed is 800-1000 rpm.
6. The method for preparing modified zinc oxide nanofibers according to claim 1, characterized in that: In S3, the drying process is carried out at a temperature of 60-100°C and for a time of 36-48 hours.
7. The method for preparing modified zinc oxide nanofiber according to claim 1, characterized in that: In S4, the calcination process is to increase the temperature to 500-700°C at a heating rate of 1-3°C / min, keep the temperature for 2-4h, and then naturally cool to room temperature.
8. A modified zinc oxide nanofiber, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.
9. An application of the modified zinc oxide nanofiber according to any one of claims 1 to 7, characterized in that: The modified zinc oxide nanofibers are used to detect 3-hydroxy-2-butanone gas, a biomarker of Listeria.
